Study of user-experience of an objective test (QbTest) to aid ADHD assessment and medication management: a multi-methods approach - Hall, Charlotte L.; Valentine, Althea; Walker, Gemma M.; Ball, Harriet M.; Cogger, Heather; Daley, David; Groom, Madeleine J.; Sayal, Kapil; Hollis, Chris (BioMed Central, 2017)
Background